Permasalahan Tarif Masuk Pelabuhan Bengkalis - Lazuardy, Akmal; Rahmani, Nur; Romadhoni, Romadhoni (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2018)
Bengkalis District is one of the districts in Indonesia which has ferriage services using roll-on roll-off ships connecting two districts: Sungai Pakning on the side of Sumatra Island and Air Putih on the side of Bengkalis Island. Since the issuance of Local Regulation No. 13 of 2011, port entrance admission has not increased yet even though there are numerous investment and infrastructure improvements on the route. The study aims at dtere The study aims to determine if tariff adjustment is required to balance the port income with its expenditure. The method used is cost and investment analysis, specifically time value of money concept. The result shows that not all consumer groups need tariff increase. Only passengers, class III vehicles, class IV-passengers, and class IV goods increased below Rp. 1,000 which need tariff adjustment while class II vehicles and class V goods increased above Rp. 1,000. The results of these calculations can be used to revise the local regulations in the future.